1 Group Bomber Command an operational record - Ward, Chris; Harrison, Greg; Korcz, Grzegorz (Pen & Sword Aviation, 2014)
A comprehensive and detailed operational history of 1 Group Bomber Command. The fifth release in a series that has already explored the records of 3,4,5 and 6 Groups.